Uji Efektivitas Daun Alamanda (Allamanda cathartica L)Terhadap Larvasida Jentik Aedes aegypti - Rasjid, Ashari; Hidayat, Hidayat; Maharanty , Nur Awalia (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Dengue fever is a serious public health problem, especially in endemic areas such as Indonesia. This disease can cause Extraordinary Events (KLB) with high mortality rates. Based on data from the Ministry of Health, until June 14, 2021, there were 16,320 cases of DHF in Indonesia, with an increase of 6,417 cases compared to the previous period. One of the efforts to control the spread of DHF is to kill Aedes aegypti mosquito larvae, the main vector of the disease. This study aims to determine the effectiveness of alamanda leaf extract (Allamanda cathartica L.) in killing Aedes aegypti larvae, using the Lethal Concentration 80 (LC80) indicator, which is the concentration that can kill 80% of the larval population. This study used a sample of 250 Aedes aegypti larvae with 3 replications for each treatment, consisting of 35%, 45%, and 50% concentrations of alamanda leaf extract, and 0% as control. The larvae were observed for 24 hours to determine the level of mortality caused by various concentrations of extracts. At 35% concentration, the total average mortality of larvae was 3 (12%). At 45% concentration, the average mortality increased to 5 (20%), and at 50% concentration, the average mortality remained at 5 (20%). These results indicate that the concentration of alamanda leaf extract used did not reach 80% mortality. Alamanda leaf extract at concentrations of 35%, 45%, and 50% is not yet effective for killing Aedes aegypti larvae because the resulting mortality percentage is still far from the LC80. Further research is needed to find more optimal concentrations or combine with other methods in mosquito larvae control. Keywords:  Alamanda Leaf Extract; Larvicide; Aedes aegypti larvae